Bottlenecks for the Sustainable Development of the Beef Value Chain in the Colombian Cauca Department - Muñoz Quiceno, Jhon Jairo; Ruíz, Lisbeth Rocío; Enciso, Karen; Puerta Rodríguez, Cristhian David; Díaz, Manuel Francisco; Charry, Andrés; Gutiérrez Solís, Jhon Freddy; Vivas Quila, Nelson J.; Morales, Sandra; Albán López, Noé; Peters, Michael; Burkart, Stefan (International Center for Tropical Agriculture, 2017)
The development of a competitive beef value chain for accessing formal and specialized national and international markets is among the principal goals of the Colombian agricultural development plans. * Cattle production in Colombia is very diverse in terms of climatic conditions, agro-ecological zones, farm sizes and production systems. * This is influencing the nature of the aligned value chains and their potential for development and for accessing more sophisticated markets. * Therefore, it is important to conduct in-depth value chain analyses and to identify the most important bottlenecks for sustainable development.